Lithuanian Picture of Mother Based on Questionnaire Data - Slotvinska, Karolina; Rutkovska, Kristina (Vilnius University Open Series, 2020)
The article performs the analysis of the concept of mother through the cognitive questionnaire methodology developed by Jerzy Bartmiński, pioneer of Polish ethnolinguistics. According to the methodology only one open question is asked to respondents: „What do you think is the essence of the true X?“ The modifier „true“ included in the question directs respondents’ attention specifically to subjective imaginations, rather than to the actual (objectively) existing typical object. Mentioning the „essence“ directs focus to the most important rather than subordinate features. During the study, the students of Vilnius University were questioned – Philology, Philosophy, History, Law, Economics and Business Administration, Medical, Physics, International Relations and Science, Mathematics and Informatics Bachelors and Masters, as well as students from Vilnius Gediminas Technical University, Antanas Gustaitis’ Aviation Institute. A total of 100 questionnaires were selected for the study: 48 questionnaires of Science dysciplines (male – 18, female – 30) and 52 questionnaires of the Humanities dysciplines (male – 20, female – 32). As the results of the analysis show, the „true mother“ is characterised in particular by psychosocial and social aspects, less often by mental, biological, household aspects. The least often the mother is characterised by physical, ethnic, religious, ethical and ideological aspects. The most common were descriptions such as: Raises, educates (S); 77, 9.2 %; Loves (A); 70, 8.4 %; Cares about (A); 65, 7.8 %; Sacrifises (A); 38, 4.5 %; Gives birth (G); 28/3.3 %; Childbirth (alone) does not constitute the presence of the mother (G); 26/3.1 %. According to the students’ opinion, it can be said that the maternity still remains a value, and its core consists of a public duty of a mother to bring up a virtuous and worthy citizen. Quite a private link between a mother and a child, which manifests in a provision of warmth and love to one another, remains important, a purely humane relationship is highly valued. Human attention does not deviate completely into sociality, his own hapiness and the happiness of his closest people is important to him.